Beginning iPhone development with SwiftUI : exploring the iOS SDK - Wang, Wally (Apress L.P., 2022)
Tame the power of Apple's new user interface toolkit, SwiftUI. Integrate all the interface elements iOS users have come to know and love, such as buttons, switches, pickers, toolbars, and sliders with less effort and more efficiency. You'll also learn about touch gestures, lists, and grids for displaying data on a user interface. And you'll even go beyond those simple controls to liven up any user interface with simple animation techniques. Spice your designs up with movement, scaling, and resizing, including spring and bounce effects! You'll start with basic designs and then explore more sophisticated ones. Assuming little or no working knowledge of the Swift programming language, and written in a friendly, easy-to-follow style, this book offers a comprehensive course in iPhone and iPad programming. The book starts with a gentle introduction to using Xcode and then guides you though the creation of your first simple application. You'll create user interfaces for that application using multiple screens in two different ways-using Navigation View and Tab Bars. Beginning iPhone Development with Swift UI covers the basic information you need to get up and running quickly to turn your great ideas into working iOS apps with stunningly interactive interfaces using SwiftUI. Once you're ready, move on to Pro iPhone Development with Swift UI to learn more of the unique aspects of iOS programming and the Swift language. What You Will Learn Discover the basics of designing a user interface using SwiftUI Build cool, crisp user interfaces that use animation Display data in lists and outlines Organize user interfaces in forms and groups Who This Book is For Aspiring iOS app developers new to the Apple Swift programming language and/or the iOS SDK.